Acceptability of contraceptive implants at the maternity ward of the Matam Communal Medical Center - Ibrahima, Conté; Momo, Soumah Aboubacar Fodé; Alpha, Diallo Boubacar; Sory, Sow Ibrahima; Aminata, Camara; Abdourahamane, Diallo; Telly, Sy; Namory, Keita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: World Health Organization (WHO), defines contraception as "the use of agents, devices, methods or procedures to decrease the likelihood of conception or avoid it". In Africa, only 24% of women of childbearing age have access to a modern contraceptive method. The objective of the study was to determine the frequency of use of the contraceptive implant, to describe the socio-demographic characteristics of the users, to identify the reasons for the choice of the method and to assess the degree of satisfaction of the clients.Methods: The study was conducted at the Matam Communal Medical Center on level 2 of the health pyramid in Guinea. This was a 12-month cross-sectional, descriptive and analytical study (June 2017 to May 2018), including all women admitted for desire for contraception and who agreed to choose the implant as a contraceptive method.Results: The study involved 512 clients. The proportion of female users was 26.21%. The average age was 27.8 years, the main users were women of liberal trade, married, multiparous. The main reasons for choice cited by clients were the effectiveness and long duration of action of the method, i.e. 35.2% and 30.9% respectively. The majority of providers of the method were represented by midwives (73.3%) and the degree of client satisfaction with the method was 97%.Conclusions: The implant is a long-acting method of contraction. It is frequently used at the Communal Medical Center of Matam. Its efficient use would involve effective counselling.